The Effect of Using the Metacognitive Learning Cycle Strategy in Developing Reading Comprehension in the Arabic Language Subject for Ninth Grade Students - Al-Mharat, Nabeel; Bani Issa, Abd’Alra’ouf (Journal of Humanities and Social Sciences Studies, 2024)
The study aimed to identify “the effect of using the metacognitive learning cycle strategy in developing reading comprehension in the Arabic language subject for ninth-grade students.” The study adopted the experimental method and the quasi-experimental design, where a reading comprehension test was prepared, consisting of (17) items. The study sample consisted of (50) students who were chosen intentionally. The results of the study showed that there was a statistically significant effect on the study sample’s scores in the reading comprehension test according to the teaching method (metacognitive learning course strategy for teaching the Arabic language, regular), and the differences were in favor of those who were exposed to For the strategy of the metacognitive learning course for teaching the Arabic language compared to individuals using the traditional method, the researcher recommends preparing a guide for the Arabic language teacher regarding reading comprehension skills and methods for developing them.